Emotional Intelligence Level Relationship with Santri Compliance Applying Pesantren Rules (SCHOOLAR: Social and Literature Study in Education, 2022)
emotional is a  must  that  belongs  to  every  student. in  boarding  schools  have  rules  and  regulations,  as  students must be able  to  comply with  the    established  by  the nanny  boarding  school  al-huda.   emotional intelligence santri  very  instrumental  to comply with  the    existing rules   dipondok  Islamic boarding school,  exemplary students  have high  emotions  to  run the rules of the cottage. This study    uses  a quantitative  approach  with  santri respondents    from one  of  the  mondok  in  pondok  Islamic boarding school  al-huda. aims  to  how much the relationship  of  emotional  intelligence  level  with  the compliance of students  in  carrying out the rules of boarding  school  Al-huda  the purpose of this  study is to  find  out  that there is a   relationship of santri  with  emotional  intelligence  in  carrying out the rules of the   cottage.   this study uses statistical  test data of  SPSS program. The results of  this study  prove  that  emotional  intelligence  has a  positive  and  significant  effect on the compliance  of  students  in  running  Islamic boarding school huts.